Bio-Fabrication of Human Amniotic Membrane Zinc Oxide Nanoparticles and the Wet/Dry HAM Dressing Membrane for Wound Healing - Ramasamy, Palaniappan; Krishnakumar, Ramachandran; Rekha, Ravichandran; Vaseeharan, Baskaralingam; Saraswathi, K.; Raj, Mohan; Hanna, Robert E. B.; Brennan, Gerard P.; Dayanithi, Govindan; Vijayakumar, Sekar (Frontiers in Bioengineering and Biotechnology, 2021)
ABSTRACT The preparation of unique wet and dry wound dressing products derived from unprocessed human amniotic membrane (UP-HAM) is described. The UP-HAM was decellularized, and the constituent proteins were cross-linked and stabilized before being trimmed and packed in sterile Nucril-coated laminated aluminium foil pouches with isopropyl alcohol to manufacture processed wet human amniotic membrane (PW-HAM). The dry type of PD-HAM was prepared by decellularizing the membrane, UV irradiating it, lyophilizing/freeze-drying it, sterilizing it, and storing it at room temperature. The UP-HAM consists of a translucent yellowish mass of flexible membranes with an average thickness of 42 µm. PW-HAM wound dressings that had been processed, decellularized, and dehydrated had a thinner average thickness of 30 µm and lacked nuclear-cellular structures. Following successful decellularization, discrete bundle of fibrous components in the stromal spongy layers, microvilli and reticular ridges were still evident on the surface of the processed HAM, possibly representing the location of the cells that had been removed by the decellularization process. Both wet and dry HAM wound dressings are durable, portable, have a shelf life of 3-5 years, and are available all year. A slice of HAM dressing costs 1.0 US$ / cm². Automation and large-scale HAM membrane preparation, as well as storage and transportation of the dressings, can all help to establish advanced technologies, improve the efficiency of membrane production, and reduce costs. Successful treatment of wounds to the cornea of the eye was achieved with the application of the HAM wound dressings. The HAM protein analysis revealed 360 µg proteins per gram of tissue, divided into three main fractions with MWs of 100 kDa, 70 kDa, and 14k Da, as well as seven minor proteins, with the 14 kDa protein displaying antibacterial properties against human pathogenic bacteria. A wide range of antibacterial activity was observed after treatment with 75 µg/ ml zinc oxide nanoparticles derived from human amniotic membrane proteins (HAMP-ZnO NP), including dose-dependent biofilm inhibition and inhibition of Gram-positive (S. aureus, S. mutans, E. faecalis, and L. fusiformis) and Gram-negative bacteria (S. sonnei, P. aeruginosa, P. vulgaris, and C. freundii).